2008
DOI: 10.1159/000118666
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of 24-Hour Infusion of Irinotecan Combined with Oral UFT for Metastatic Colorectal Cancer

Abstract: Background: To evaluate the efficacy and safety of irinotecan combined with UFT for untreated and pretreated metastatic colorectal cancer. Methods: Escalating doses of irinotecan (80–110 mg/m2) were administered by 24-hour infusion on day 1. UFT was administered orally at 400 mg/m2/day on days 3–7 and 10–14. The treatment cycles were repeated every 2 weeks. Results: In the phase I study, the maximum tolerated dose of irinotecan was 110 mg/m2 and the recommended dose for the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…We previously conducted a phase I/II study of a combination regimen consisting of biweekly 24-hour infusion of irinotecan and 2 days off/5 days on of UFT without LV [8]. In September 2003, oral LV became available in Japan, and we successively conducted this phase I/II study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted a phase I/II study of a combination regimen consisting of biweekly 24-hour infusion of irinotecan and 2 days off/5 days on of UFT without LV [8]. In September 2003, oral LV became available in Japan, and we successively conducted this phase I/II study.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate was 62.9%, including 3 patients with a complete response, and the PFS was 5.6 months. No patient had grade ≥3 nonhematologic toxicity [19]. In a subsequent phase I/II study evaluating a 24-hour continuous intravenous infusion of irinotecan combined with oral UFT plus leucovorin in patients with MCRC, the response rate was 63.9%, including 4 patients who had a complete response, and the PFS was 8.3 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytotoxic effects of irinotecan are specific to the S-phase of the cell cycle, and low doses of irinotecan given by protracted infusion or frequent bolus injection can prevent the saturation of carboxylesterases, enzymes that convert irinotecan to its active metabolite SN-38, and thereby enhance antitumor activity [17,18]. We have previously performed phase I/II clinical studies of a 24-hour continuous intravenous infusion of irinotecan, given every 2 weeks, combined with oral UFT and with oral UFT plus leucovorin in patients with MCRC and reported that these regimens are therapeutically useful and have low incidences of diarrhea and other adverse events [19,20]. However, there has been no randomized clinical trial comparing a 24-hour continuous infusion to the standard 90-min infusion of irinotecan up to now.…”
Section: Introductionmentioning
confidence: 99%
“…UFT, a combination of the oral 5-FU prodrug tegafur and uracil in a molar ratio of 1: 4, is an orally administered fluoropyrimidine that provides similar 5-FU pharmacokinetics to continuous-infusion 5-FU [9] . Irinotecan plus UFT [10] or UFT with LV is an effective and well-tolerated regimen for the first-line treatment of mCRC [11][12][13] . UFT combined with 5-FU HAI significantly decreased hepatic recurrences in patients after curative resection of liver metastases [14] .…”
Section: Introductionmentioning
confidence: 99%